FORMS AND METHODS OF TEACHING DISCIPLINE "ECOLOGICAL EXPERTISE" FOR STUDENTS ECOLOGISTS - RIDEI, Nataliia; PALAMARCHUK, Svetlana (Trends in education, 2012)
The article deals with the forms and methods, the analysis of the content of the subject "Environmental assessment" for student environmentalists highlighted the main criteria of knowledge and skills in the study of the course. Submitted characteristics and structure of discipline and learning activities.
Keywords: ecological expertise; skill analysis; the structure of discipline; training activities.